Determination of Inorganic Ion Profiles of Illicit Drugs by Capillary Electrophoresis. Issue 6 (29th August 2016) - Evans, Elizabeth; Costrino, Carolina; do Lago, Claudimir L.; Garcia, Carlos D.; Roux, Claude; Blanes, Lucas
Abstract: A portable capillary electrophoresis instrument with dual capacitively coupled contactless conductivity detection (C 4 D) was used to determine the inorganic ionic profiles of three pharmaceutical samples and precursors of two illicit drugs (contemporary samples of methylone and para‐methoxymethamphetamine). The LODs ranged from 0.10 μmol/L to 1.25 μmol/L for the 10 selected cations, and from 0.13 μmol/L to 1.03 μmol/L for the eight selected anions. All separations were performed in less than 6 min with migration times and peak area RSD values ranging from 2 to 7%. The results demonstrate the potential of the analysis of inorganic ionic species to aid in the identification and/or differentiation of unknown tablets, and real samples found in illicit drug manufacture scenarios. From the resulting ionic fingerprint, the unknown tablets and samples can be further classified.